PROGRAM BIMBINGAN BACA TULIS AL QUR’AN BAGI ANAK BERKEBUTUHAN KHUSUS (AUTIS) DI SD AL AZZAM KETILENG SEMARANG - Kholfan Zubair Taqo Sidqi (LP2M, 2018)
This article discusses guidance program Read Qur'an for children with special needs. Theresults show that a number of conditions (multi / many factors) affect the brain developmentof autistic children that occurred since the age of 6 months in the womb and continue in life,where genetic factors (heredity) is a very influential factor. These brain developmentdisorders cause problems with language skills, cognitive ability (comprehension), socialinteraction ability, and adaptive function, hence this causes the increasing age of a child willlead to greater gap / different abilities compared with other children as peer age, so the morevisible differences with children peer age / his age. All of these things can be clearly seenbefore the child is 3 (three) years old, and the age will be more visible.Keywords: Guidance to Read Al Qur'an, Autism